CAMEL ANALYSIS OF FINANCIAL PERFORMANCE IN SHARIA BANK ON THE INDONESIAN STOCK EXCHANGE - Fajriyani, Fajriyani; Sri Wahyuni Nur (Funds: Jurnal Ilmiah Akuntansi, Keuangan, dan Bisnis, 2023)
Financial Performance is a description of the achievements achieved by the company in its operational activities, both regarding financial aspects, marketing aspects, fund collection aspects and fund distribution. This research aims to determine the financial performance of Sharia Banks, namely BRI Syariah, Bank Panin Dubai Syariah and BTPN Syariah using CAMEL analysis. This research uses CAMEL analysis, which is a measuring tool that measures banking health performance. The ratios used consist of CAR, NPF, NPM, ROA, BOPO and FDR ratios using quantitative data sourced from financial reports from the Indonesian Stock Exchange. Data collection uses documentation methods. The results of this research show that Financial Performance with capital analysis using the CAR ratio of BRI Syariah is in a very healthy condition, BTPN Syariah is in a very healthy condition and Bank Panin Dubai Syariah is in a very healthy condition. Asset analysis uses the NPF ratio of BRI Syariah in a fairly healthy condition, BTPN Syariah in a very healthy condition and Bank Panin Dubai Syariah in a healthy condition. Management analysis uses the NPM ratio of BRI Syariah in an unhealthy condition, BTPN Syariah in an unhealthy condition and Bank Panin Dubai Syariah in a very healthy condition. Earnings analysis uses the ROA ratio of BRI Syariah in an unhealthy condition, Bank Panin Dubai Syariah in an unhealthy condition and BTPN Syariah in a very healthy condition, BRI Syariah BOPO ratio in a very healthy condition, BTPN Syariah in a very healthy condition and Bank Panin Dubai Syariah in a very healthy condition. very healthy. Liquidity analysis uses the FDR ratio of BRI Syariah in a healthy condition, BTPN Syariah in a fairly healthy condition and Bank Panin Dubai Syariah in a fairly healthy condition. Keywords :